Does fetuin-A mediate the association between pro-inflammatory diet and type-2 diabetes mellitus risk? - Toprak, Kadriye; Görpelioğlu, Süleyman; Özsoy, Ahmet; Özdemir, Şeyda; Ayaz, Aylin (Nutrición hospitalaria : organo oficial de la Sociedad Española de Nutrición Parenteral y Enteral, 2022)
Introduction: recent studies indicate that diet increases T2DM risk via inflammation. Fetuin-A, identified as an acute-phase protein, plays a role in insulin resistance and is an independent predictor of type-2 diabetes. Objectives: the present study aimed to examine the association between diet and T2DM risk, and whether said association is mediated by fetuin-A, and to determine the effect of fetuin-A on T2DM risk. Methods: the case group included 40 individuals with T2DM, whereas 40 individuals without T2DM comprised the control group. The Dietary Inflammatory Index (DII), was used to determine the inflammatory potential of diet. A simple mediation analysis was used to investigate whether diet was associated with T2DM risk and whether the association was mediated by fetuin-A. Results: subjects who consumed a high pro-inflammatory diet had 2.0 times higher risk of developing T2DM (OR = 2.043; 95 % CI: 0.955 to 4.371, p = 0.066). In addition, subjects who had higher levels of fetuin-A had a 1,2 times higher risk of developing T2DM (OR = 1.155; 95 % CI: 1.030 to 1.296, p = 0.014). Both fetuin-A and hs-CRP had a significant full mediator role on the association between DII and HOMA-IR [respectively; β = 0.371 (95 % CI: -0.029-0.770), β = 0.424 (95 % CI: -0.007-0.856)]. Conclusion: these findings suggest that a pro-inflammatory diet, by creating an environment of increased inflammatory markers, affects in particular insulin resistance through these markers and ultimately causes T2DM. In addition, fetuin-A also acts as an important novel mediator between diet and T2DM by inducing insulin resistance.